Bond Prices Through Bond Ranking As Intervening Variables: Liquidity, Leverage , Company Size, Auditor's Reputation - Sukma Maskami; Ramdani Bayu Putra; Muhammad Pondrinal (Yayasan Riset dan Pengembangan Intelektual, 2022)
The purpose of this study was to determine the effect of liquidity, leverage, firm size, auditor reputation and bond ratings on bond prices. This type of research data obtained from secondary data. The sample in this study were 48 companies listed on the Indonesia Stock Exchange using the random sampling method. The results of this study indicate that liquidity, leverage, firm size, auditor reputation have no effect on bond ratings and leverage, firm size, auditor reputation have a positive and significant effect on bond prices, while liquidity, leverage, firm size, auditor reputation affect bond prices through bond rating. Keywords: bond prices, liquidity, leverage, firm size, auditor